E-Field Uniformity Test Volume In Gtem Cell Based On Labview (International Journal of Engineering and Computer Science, 2017)
The standard IEC 6100-4-20 is used to carry out field uniformity in GTEM 5407 using Labview as the controlling software. For reliable and reproducibility of measurements in the GTEM, determine the field distribution to ensure the field uniformity for the performance of emissions and immunity tests is a requirement. In this work the determination of electric field distribution which is a lengthy process is carried out employing the Labview software for automatic capturing and storage at each point of measurement all the needed parameters in the frequency range of interest. The selected working volume chosen showed the primary field within 0 – 6dB required by the standard as well as – 6dB cross coupling separation. The GTEM working volume was prepared for total radiated power test for GSM900 phone.